Wang's Forceps‐Assisted Percutaneous Insertion and Fixation of Peritoneal Dialysis Catheter. Issue 7 (30th March 2018) - Wang, Huiming; Wang, Yujuan; Zhu, Jili; Chen, Xinghua; Chen, Cheng; Xiang, Cuizhi; Jia, Houjun; Ding, Guohua
Abstract: Percutaneous insertion of peritoneal dialysis catheters is theoretically most preferred by nephrologists because of the advantages of bedside performing, surgery independence, and minimal injury over other procedures of catheter placement such as open surgical dissection or laparoscopic operation. However, blindly placing catheters in the percutaneous procedure brings the risk of catheter malposition or bowel perforation; this largely retarded it's implementation. We had previously developed a novel technique termed "Wang's forceps‐assisted catheter insertion and fixation, " which had been successfully applied in the open surgical catheter insertion and displaced catheter reposition in our center. In this study, we further explored the possibility of applying the Wang's forceps in the procedure of percutaneous catheter insertion both in porcine model and patients with end stage renal disease (ESRD). A total of three miniature pigs successfully received percutaneous catheter insertion using Seldinger's technique with Wang's forceps assistance. The catheters were all placed in the right position and functioning well in dialysate drainage. This novel method of percutaneous catheter insertion was then performed on 20 ESRD patients. The procedure showed effective time‐saving with the average operating time of 29.2 ± 3.53 min and was well tolerated by patients with minimal pain and injury. During a follow‐up time of 6 months, no complications of catheter displacement, leakage, or blockade occurred. Our preliminary observation demonstrates that utilization of Wang's forceps in a percutaneous procedure conferred benefits of accurately placing and fixing catheters while preserving the merits of minimal invasion and simple performance.